KERATOCONUS IN NORTH INDIA: A DEMOGRAPHIC AND CLINICAL PROFILE STUDY - Dr Kavya Bansal; Dr Rupali Kashyap; Dr Tanvi Gupta; Dr Tanisha Mittal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Purpose: To evaluate the demographic profile and clinical characteristics of newly diagnosed patients with keratoconus (KC) in North India and to analyze the relationship between age, sex, and disease severity.Methods: A cross-sectional observational study was conducted at a tertiary eye care hospital between August 2020 and July 2022. Two hundred sixty-eight consecutive patients with clinically confirmed KC were included. Each underwent comprehensive evaluation, including visual acuity testing, slit-lamp biomicroscopy, and corneal imaging with the Sirius (CSO, Florence, Italy) systems [8]. Data regarding age, sex, and maximum keratometry (K max) were collected. KC severity was graded using K max. Statistical analyses were performed using SPSS v20, with p < 0.05 considered significant.Results: The mean self-reported age at first presentation was 19.3 ± 6.1 years, and the mean age at diagnosis was 20.4 ± 6.0 years (range 4–43). Of the total patients, 62% (n = 166) were male and 38% (n = 102) were female. The mean K max was 59.4 ± 13.2 D. Most patients were diagnosed between 14 and 23 years, presenting with moderate-to-severe disease (K max = 51–61 D). Pediatric KC (≤ 18 years) accounted for 39% (n = 104), while adult KC (> 18 years) comprised 61% (n = 164). Pediatric cases showed significantly higher mean K max (62.1 ± 15.0 D) than adults (57.2 ± 11.4 D, p < 0.01). A weak negative correlation between age and K max (r = –0.21, p = 0.04) indicated a mild decline in severity with increasing age [9].Conclusion: KC in North India presents predominantly in late adolescence and early adulthood with a male predominance [2]. Pediatric KC tends to be more severe. Regional screening and awareness programs are essential for early detection and intervention